Deconstructing service-learning : research exploring context, participation, and impacts - Billig, Shelley H.; Eyler, Janet; Furco, Andrew (Advances in service-learning research., 2003)
This work looks at service learning. It cover such topics as: challenges for service-learning research; enhancing theory-based research on service learning; dilemmas of service learning teachers; the diffusion of academic service learning in teacher education; and more.